Bee species visiting Medicago sativa differ in pollen deposition curves with consequences for gene flow. Issue 6 (10th June 2021) - Santa‐Martinez, Emmanuel; Cardoso Castro, Cibele; Flick, Andrew; Sullivan, Michael; Riday, Heathcliffe; Clayton, Murray K.; Brunet, Johanne
Abstract : Premise: Pollinator foraging behavior can influence pollen dispersal and gene flow. In many plant species a pollinator trips a flower by applying pressure to release its sexual organs. We propose that differences in tripping rate among grooming pollinators could generate distinct pollen deposition curves, the pattern of pollen deposition over successive flowers visited. This study compares the pollen deposition curves of two grooming pollinators, a social bumble bee and a solitary leafcutting bee, with distinct tripping rates on Medicago sativa flowers. We predict a steeper deposition curve for pollen moved by leafcutting bees, the pollinator with the higher tripping rate. Methods: Medicago sativa plants carrying a gene (GUS) whose product is easily detected by staining, were used as pollen donors. After visiting the GUS plants, a bee was released on a linear array of conventional M. sativa plants. The number of GUS pollen grains deposited over successive flowers visited or over cumulative distances was examined. Distinct mixed effect Poisson regression models, illustrating different rates of decay in pollen deposition, were fitted to the pollen data for each bee species. Results: Pollen decay was steeper for leafcutting bees relative to bumble bees for both models of flowers visited and cumulative distance, as predicted by their higher tripping rate. Conclusions: This is the first report of a difference in pollen deposition curves between two bee species, both grooming pollinators. Such differences could lead to distinct impacts of bee species on gene flow, genetic differentiation, introgression, and ultimately speciation.